Developing A Reading Project Assessment to Stimulate Students’ Critical Thinking and Creativity - Ramdani, Aldin Syah; Linggar Bharati, Dwi Anggani; Mujiyanto, Januarius (English Education Journal, 2021)
Assessment is a part of the learning assessment phase of the teaching and learning process. It is used to evaluate whether the education goals have been reached by looking at the process and product of learning outcomes. However, many teachers need assistance in developing a suitable assessment system and instrument. Then it should be in line with the teaching and learning priorities of the 2013 curriculum, which enable teachers to challenge students' analytical and creative thinking. This study aimed to explain the development of project-based reading assessments to stimulate students' critical thinking and creativity of the tenth graders of X IPS 3 at SMAN 12 Semarang during the academic year 2018/2019. To construct project-based reading assessments, the researcher and the teacher collaborated. The module was revised based on expert advice until the main field testing was completed. The data collection methods were using a questionnaire, interview, observation, and examination to obtain quantitative and qualitative data. The study discovered that when students were given project-based reading assessments, their scores increased. According to the results of a paired sampled test, the students' mean score changed significantly after the post-test relative to the pre-test. Students' comprehension skills, critical thinking, and creative thinking have all improved as a result of project-based reading assessments. In conclusion, the project based assessment is applicable for teaching learning activities to stimulate high school students’ critical thinking and creativity.